(3cJGFH CYdGe GdCNHGQ ef abgGA ePgH GdfYeGf GdeNJGQs - (3Gdcahj , eMehO Hf SdjeGf GdMfaj GdQhej,J (B990 (3g` s
(3ChdgG (B:s
(3hHYO , aEf SfI Gddg Cf jMOK ai cd YUQ ef GdCYUGQ WGFaI ef GdYdeGA ai GdeOGFf hGdCeUGQ hdbO cfG ai CKfGA HYV GddjGdifSGgQ GdHdGO hGdCbGVi s
(3BNQgG (B:s
(3NGJeI GdcJGH LGeYI GdZQGFH SHMGfc Gdge CfJ MSHj hfYe Gdhcjd s
(3GfXQ HQbe (B" 389" (3JGQjNs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B168s
(3HQhcdeGf (B- (3GdLRA (B4 - (3U (B434 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B645 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B331 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs